Localizing the lipid products of PI3Kγ in neutrophils. (January 2016) - Norton, Laura; Lindsay, Yvonne; Deladeriere, Arnaud; Chessa, Tamara; Guillou, Hervé; Suire, Sabine; Lucocq, John; Walker, Simon; Andrews, Simon; Segonds-Pichon, Anne; Rausch, Oliver; Finan, Peter; et al.
Abstract: Class I phosphoinositide 3-kinases (PI3Ks) are important regulators of neutrophil migration in response to a range of chemoattractants. Their primary lipid products PtdIns(3, 4, 5)P3 and PtdIns(3, 4)P2 preferentially accumulate near to the leading edge of migrating cells and are thought to act as an important cue organizing molecular and morphological polarization. We have investigated the distribution and accumulation of these lipids independently in mouse neutrophils using eGFP-PH reportersand electron microscopy (EM). We found that authentic mouse neutrophils rapidly polarized their Class I PI3K signalling, as read-out by eGFP-PH reporters, both at the up-gradient leading edge in response to local stimulation with fMLP as well as spontaneously and randomly in response to uniform stimulation. EM studies revealed these events occurred at the plasma membrane, were dominated by accumulation of PtdIns(3, 4, 5)P3, but not PtdIns(3, 4)P2, and were dependent on PI3Kγ and its upstream activation by both Ras and Gβγs.